The 14-3-3 Protein Family and Schizophrenia - Navarrete, Meaghan; Zhou, Yi (Frontiers in Molecular Neuroscience, 2022)
Schizophrenia is a debilitating mental disorder that affects approximately 1% of the world population, yet the disorder is not very well understood. The genetics of schizophrenia is very heterogenous, making it hard to pinpoint specific alterations that may cause the disorder. However, there is growing evidence from human studies suggesting a link between alterations in the 14-3-3 family and schizophrenia. The 14-3-3 proteins are abundantly expressed in the brain and are involved in many important cellular processes. Knockout of 14-3-3 proteins in mice has been shown to cause molecular, structural, and behavioral alterations associated with schizophrenia. Thus, 14-3-3 animal models allow for further exploration of the relationship between 14-3-3 and schizophrenia as well as the study of schizophrenia pathology. This review considers evidence from both human and animal model studies that implicate the 14-3-3 family in schizophrenia and discusses. In addition, possible mechanisms by which alterations in 14-3-3 proteins may contribute to schizophrenia-like phenotypes. such as dopaminergic, glutamatergic, and cytoskeletal dysregulations are discussed.